ACFTA (ASEAN -CHINA Free Trade Area): Menguntungakan Atau Merugikan Indonesia ? Ditinjau dari Perspektif Neoliberalisme - Sinta Julina (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2022)
The background of the research is that globalization causes rapid changes in various dimensions in international relations, so that countries in the world absolutely must cooperate between countries. Similarly with countries in Southeast Asia (ASEAN) and China, they believe that international cooperation can provide strength to face regionalism and economic blocs. Therefore they agreed to carry out free trade cooperation ACFTA then inaugurated the free trade of ASEAN and China in January 2010. In November 2018 President Joko Widodo finally ratified the "Protocol to Amend the Framework Agreement on Comprehensive Economic Co-operation and Certain Agreements thereunder between ASEAN and the People's Republic of China (2015). ACFTA is an agreement between ASEAN member countries and China to create a free trade area by eliminating or reduce barriers to trade in goods, both tariff and non-tariff, increase market access for services, investment rules and regulations. Even though it's already implementation of the ACFTA is still causing differences of opinion. Many are optimistic about accepting the implementation of ACFTA as something beneficial. However, not a few are also skeptical and pessimistic about the implementation of ACFTA because it is seen as detrimental to Indonesia. The purpose of this study is to examine whether ACFTA benefits or harms Indonesia? from the perspective of neoliberalism. To analyze and answer the formulation of the problem, the author uses the Neoliberalism Perspective. = The results of this study are viewed from the perspective of Neoliberalism, ACFTA has proven to be profitable for Indonesia.